Long-stay and ageing - Di Lorito, Claudio (Springer, 2018)
Older forensic psychiatric patients stay in secure services longer than prisoners sentenced for the same offence, patients in general psychiatric settings and forensic psychiatric patients of all ages. Prolonged stay may reflect that service provision is far from meeting the unique needs of this population, but research in this area is very limited. Drawing from the existing literature in forensic psychiatry and in other restrictive settings, this chapter aims to: (i) present data on older patients in relation to their prevalence in forensic psychiatric settings, sociodemographic characteristics, violence, mental health and individual needs; (ii) present data on length of stay in comparison with other populations in secure care; (iii) report and discuss issues around the long-term care of older patients, including physical health care, the presence of cognitive impairment and dementia, (the potential development of) national long-term units for patients with intensive care needs and the need for age-relevant treatment and activities. Potential implications for service improvement in relation to policy making and research are also discussed.